Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1002/(sici)1521-186x(1999)20:2<123::aid-bem7>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Changes of hydration of rats' tissues after in vivo exposure to 0.2 Tesla steady magnetic field

Abstract: Hydration and [3H]ouabain uptake by different tissues of adult male rats were measured immediately after exposure to homogenous 0.2 T steady magnetic field. A time‐dependent decrease of hydration and adaptation, followed by disadaptation, was detected in brain and liver tissues in most of the rats after 3.5–5 h of exposure. The number of functional active ouabain binding receptors, which correlates with cell volume, was also decreased in brain, liver, and spleen and increased in kidney tissue after half an hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Our previous studies have shown that SMF exposure leads to cell dehydration, including the heart muscle of adult rats [Danielyan and Ayrapetyan, 1999]. The present study on animals of different ages indicates that SMF exposure has significant (21%) dehydration effects on the heart muscle of young animals, while the dehydration of heart muscles of older animals is insensitive to SMF (Fig.…”
Section: Resultssupporting
confidence: 57%
“…Our previous studies have shown that SMF exposure leads to cell dehydration, including the heart muscle of adult rats [Danielyan and Ayrapetyan, 1999]. The present study on animals of different ages indicates that SMF exposure has significant (21%) dehydration effects on the heart muscle of young animals, while the dehydration of heart muscles of older animals is insensitive to SMF (Fig.…”
Section: Resultssupporting
confidence: 57%
“…Moreover, it is known that, because of intracellular macromolecules functioning in aqua medium, the cell hydration plays also a key role in the regulation of their functional activity (Parseghyan et al 2000). On the basis of these data, we have suggested that abnormal cell hydration is an important factor in the generation of pain (nociceptive) signals in nerve terminals and has an important role in other forms of cell pathology (including cancer, nervous, and cardiovascular disorders) (Ayrapetyan 1998;Danielian et al 1999). Therefore, the cell hydration was suggested as a potential cellular marker through which the biological effect of different environmental factors are realized.…”
mentioning
confidence: 92%
“…It was previously shown that SMF exposure had dehydration effects on different cells of rats (Danielian and Ayrapetyan, 1999). Therefore, NIR-treated PS effect on potential-activated ionic current and agonist activated ionic current through the membrane in isolated neurons of snails was studied Hunanyan and Ayrapetyan, 2007).…”
Section: Nir-treated Physiological Solution (Ps) Effect On Functionalmentioning
confidence: 99%